Constructions of credibility in decisions concerning unaccompanied minors. Issue 2 (12th June 2017) - Hedlund, Daniel
Abstract : Purpose: The purpose of this paper is to explore the key credibility principles used by Migration Agency case-officers in Sweden. More specifically it analyses how they construct arguments about asylum-seeking unaccompanied minors' credibility in first-decisions. Design/methodology/approach: The study is inspired by a social constructionist approach to discourse and explore how case-officers construct legally legitimate arguments about credibility. The qualitative text analysis is focused on discursive practice. The data selected for analysis consists of 827 excerpts containing case-officers' credibility reasoning deducted from a sample of 916 decisions. Findings: The main finding is that case-officers question unaccompanied minors by using argumentative techniques in which children appear to be expected to deliver detailed and coherent accounts. In addition, unaccompanied minors' knowledge-claims can be questioned regardless of decision outcome (rejection or approval). As unaccompanied minors' claims for asylum appear to be questioned in such an extensive manner, their humanitarian claims also seem to be reduced. The findings of this study suggest that there is a risk that the possibility to be understood as a legitimate asylum seeker, worthy of residency, can be restricted for unaccompanied minors. Practical implications: The findings indicate that when case-officers base their understanding of credibility on unaccompanied children's individual life experiences they make use of a limited repertoire of arguments. Originality/value: This study contributes to insights about how case-officers fulfil legal expectations when assessing unaccompanied minors' credibility. The findings can be of interest to both legal and social science as well policy planners and immigration practitioners.